Prognostic value of radiologically enlarged lymph nodes in patients with metastatic colorectal cancer: Subgroup findings of the randomized, open-label FIRE-3/AIO KRK0306 trial. Issue 100 (March 2018) - Hofmann, Felix O.; Holch, Julian W.; Heinemann, Volker; Ricard, Ingrid; Reiser, Maximilian F.; Baumann, Alena B.; Hesse, Nina; D'Anastasi, Melvin; Modest, Dominik P.; Stintzing, Sebastian; Sommer, Wieland H.
Highlights: Metastatic colorectal cancer patients were screened for enlarged lymph nodes (LN). LN were evaluated in standard baseline computed tomographies. Enlarged LN correlate with established negative prognostic parameters. Enlarged LN are associated with a reduced overall survival. Enlarged LN influence prognosis beyond established prognostic parameters. Abstract: Purpose: To determine the prognostic impact of radiologically enlarged lymph nodes ≥ 10 mm on the survival of patients with metastatic colorectal cancer. Materials and methods: The prospective, randomized, open-label FIRE-3/AIO KRK0306 trial evaluated the first-line therapy of patients with KRAS exon 2 wild-type metastatic colorectal cancer with fluorouracil, folinic acid and irinotecan plus either cetuximab or bevacizumab. In the RAS wild-type population (n = 400), adequately evaluable baseline computed tomographies (n = 339) were reviewed for enlarged regional and distant lymph nodes. Their prognostic relevance was retrospectively analyzed in uni- and multivariable Cox proportional hazard regressions. Results: Median overall survival was 21.7 months in patients with enlarged lymph nodes and 33.2 months in patients without (hazard rate ratio [HR] = 1.61, 95% confidence interval [CI], 1.23–2.09; P < 0.001). This was confirmed in multivariable analysis (HR = 1.37, 95% CI, 1.02–1.83; P = 0.036). Progression-free survival of patients with enlarged lymph nodes showed a consistent but insignificant trend (9.9 vs. 11.1 months; HR = 1.23, 95% CI, 0.98–1.54; P = 0.072). Enlarged lymph nodes were also associated with BRAF-mutations ( P = 0.004). Conclusion: The presence of radiologically enlarged lymph nodes in baseline staging has a negative prognostic value beyond established and potential prognostic parameters.